GAMBARAN GAYA HIDUP SEHAT PADA KLIEN HIPERTENSI (STUDY LITERATUR REVIEW) - Diana Nur Hidayanti Tanjung; Lia Meilianingsih; Tati Suheti; Achmad Husni (UPPM. Poltekkes Kemenkes Bandung, 2021)
Hypertension is a condition where a person experiences an increase in blood pressure above normal which results in an increase in morbidity and mortality / mortality. This research is motivated by the increasing incidence of hypertension in Indonesia. The incidence of hypertension in Indonesia is 34.1% which previously in 2013 amounted to 31.7%. While the incidence rate in West Java is 43%. This study aims to find a picture of